Congenital Malformation at Gunung Wenang Hospital Manado : A Five-Year Spectrum - Nurhayati Masloman; I. Mustadjab; Muzief Munir (Indonesian Pediatric Society, 1991)
A five-year evaluation of congenital malformation among newborn infants born at Gunung Wenang Hospital has been evaluated in an attempt to get the picture of the congenital malformation spectrum and the magnitude of its problems in Manado, Indonesia.The total incidence of congenital malformation in this study was 0.9 %, of which 0.5 % were major types. The most common-major malformation were : cleft lip and palate, talipes, multiple malformation, anal atresia, ompha/ocele and congenital heart diseases. The minor types were: abnormal formation of the ears, incomplete descensus of the testis, hydrocele and finger defects. The risk of having a newborn with birth defects was highest among mother's first pregnancy and among grande multiparity.